COMMENT ON THE ARTICLE «SOLID CaCO3 FORMATION IN WATERS OF CIRCULATING COOLING SYSTEMS OF POWER PLANTS UNDER THE CONDITIONS OF ELECTRIC LOAD CHANGE» - Kochmarskii, V. Z. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2020)
In article [Kochmarskii, 2018] in the analysis of the Ist stability index and the rate of the formation of calcium carbonate Dve from circulated water (CW) of the cooling systems of electric power stations with cooling towers under changeable electric load Ne the direct dependence of dynamic parameter φ on Ne has not been taken into account. In some cases this led to inadequate reflection of Ist(Ne) and Dve(Ne) dependences. This inadequacy has been taken into account and proper laws of the expected value have been obtained. It was shown that the rate of the formation of calcium carbonate Dve is proportional to the electric load of the electric power station, to the concentration of Ca2+ ions in feed water and to the fraction of the heat used which is dispersed by evaporation at cooling towers, and it is inversely proportional to the water volume of circulated cooling system (CСS) and the average efficiency (AE) of the station.